Prognostic values of gray matter to white matter ratios on early brain computed tomography in adult comatose patients after out-of-hospital cardiac arrest of cardiac etiology. (November 2015) - Lee, Byung Kook; Jeung, Kyung Woon; Song, Kyoung Hwan; Jung, Yong Hun; Choi, Wook Jin; Kim, Soo Hyun; Youn, Chun Sung; Cho, In Soo; Lee, Dong Hun; ,
Abstract: Aim of the study: Previous studies found that the gray matter to white matter ratio (GWR) on brain computed tomography (CT) could be used to predict poor outcomes in cardiac arrest survivors. However, these studies have included cardiac arrests of both cardiac and non-cardiac etiologies. We sought to evaluate if the GWR on brain CT can help to predict poor outcomes after out-of-hospital cardiac arrest (OHCA) of cardiac etiology. Methods: Using a multicenter retrospective registry of adult cardiac arrest survivors treated with therapeutic hypothermia, we identified survivors of OHCA of cardiac etiology who underwent brain CT within 24 h after successful resuscitation. Gray and white matter attenuations were measured, and the GWRs were calculated as in previous studies. The prognostic values of the GWRs were analyzed, and a logistic regression analysis was performed to determine the contribution of the GWR in predicting poor outcomes (Cerebral Performance Category 3–5). Results: of 283 included patients, 140 had good outcomes and 143 had poor outcomes. Although the GWRs could predict poor outcomes with statistical significance, the sensitivities were remarkably low (3.5% to 5.6%) at cutoff values with 100% specificity. No significant difference in predictive performance was found between the primary predictive model, containing independent poor outcome predictors, and the primary predictive model combined with the GWR. Conclusion: In a cohort of comatose adults after OHCA of cardiac etiology, the GWR demonstrated poor predictive performance and was not helpful in predicting poor outcomes.